A Rare Case of Allergic Fungal Rhinosinusitis in Indonesian Elderly: A case Rport and Diagnostic Procedure - Drean Ferrys Widhiono, -
Abstract Background Allergic fungal rhinosinusitis (AFRS) is a rare case.